Study of plasma homocysteine level in patients with bronchial asthma and its relation to asthma severity - Ramadan S Abdel-Aziz; Ahmed S Al Adl; Mohammad M Alsayyad; Tarek M Emaran; Hesham Abdelsamee (Wolters Kluwer Medknow Publications, 2018)
Background Homocysteine (HCY) may play a role in activation of immune system in some chronic diseases, like asthma and chronic obstructive pulmonary disease. Aim The aim was to study the plasma HCY values in patients with bronchial asthma and its correlation to asthma severity. Patients and methods A total of 80 patients were enrolled, and their ages ranged from 20 to 40 years. The study populations were categorized into three groups: high reversibility asthma (n=30), low reversibility asthma (n=30), and healthy nonasthmatics (Controls n=20). For all patients, full history taking, clinical examination, chest radiography, routine laboratory investigations, pulmonary function tests, and the HCY and immunoglobulin E levels were estimated. Results The HCY measurements were found to be 8.7±0.6 µmol/l in the control group, 5.5±0.2 µmol/l in patients with high reversibility asthma, and 6.1±0.8 µmol/l in patients with low reversibility asthma. So, there was a significant variance between studied groups regarding HCY levels, but both high and low reversibility groups had low HCY when compared with control group. Moreover, the high reversibility asthma had low HCY levels when compared with low reversibility groups but without significant difference. Conclusion Plasma HCY levels, instead of being increased, may be in the low normal range or decreased in patients with asthma, most probably owing to hypoxia and in the absence of factors leading to increased HCY levels.